Psychological well-being of office employees and workplace space organization. A review of theoretical approaches - J.G. Panyukova; E.S. Alexandrova (Современная зарубежная психология)
Context and relevance. The article presents a review of theoretical approaches devoted to the analysis of the relationship between the psychological well-being of an office employee and the organization of the workplace space. Objective. The content of the selected theories is briefly stated, and the reference to modern empirical research illustrates certain provisions of these theories. Methods and materials. The analysis of the studies was carried out from 2020 to 2024, using the ScienceDirect search engine and was limited to publications in the periodicals «Journal of Environmental Psychology» and «Building and Environment». Results. Within the framework of the environmental approach, emphasis is placed on determining the «correspondence» of the organization of the spatial environment of the office (office type) to the subjectively perceived productivity, satisfaction and attachment to the workplace. The organizational-psychological approach focuses on the mental states of employees (stress, exhaustion, burnout, etc.) associated with the organization of office space. Within the framework of the evolutionary-psychological approach, the characteristics of the organization of the workplace space are considered, which determine the preferences of the subject in choosing the features of the organization of the workplace space. Conclusions. Based on the review of theoretical approaches, the following groups of theories have been identified: theories focused on the study of various indicators of the organization of office space; theories focusing on a certain «effect» of interaction between an employee and the organization of office space: «attachment to place" (environmental approach); «privacy», made in the format of a socio-psychological approach; «workplace control», the interpretation of which is undertaken in cognitive-behavioral psychology; theories within the framework of which certain factors are singled out, for example, personological or organizational-cultural, when the features of interrelations in the system «mental functioning of an employee — organization of the workplace space» are considered as mediated by certain factors: temperamental, personal characteristics, type of organizational culture, etc.